The invertebrate host of salmonid fish parasites Ceratonova shasta and Parvicapsula minibicornis (Cnidaria: Myxozoa), is a novel fabriciid annelid, Manayunkia occidentalis sp. nov. (Sabellida: Fabriciidae) - Atkinson, Stephen D.; Bartholomew, Jerri L.; Rouse, Greg W. (Zootaxa, 2020)
Myxosporea (Cnidaria: Myxozoa) are common fish parasites with complex life cycles that involve annelid hosts. Two economically important salmonid-infecting myxosporeans from rivers of the northwestern United States, Ceratonova shasta (Noble, 1950) and Parvicapsula minibicornis Kent et al., 1997, have life cycles that require a freshwater annelid host, identified previously as Manayunkia speciosa Leidy, 1859. This species was described originally from Pennsylvania, with subsequent records from New Jersey, the Great Lakes and west coast river basins. Despite apparent widespread distributions of both suitable fish hosts and the nominal annelid host, both parasites are restricted to river basins in the northwestern US and have never been recorded from the Great Lakes or the eastern US. In this study, we sampled 94 infected and uninfected annelids from two northwestern US rivers to confirm the identity of the host. We found these new specimens had mitochondrial COI sequences with no more than 4.5% distance from each other, but with at least 11% divergence from M. speciosa sampled from near the type locality (New Jersey) and Lake Superior. We did not recover any M. speciosa from either west coast river. The annelid from the Klamath and Willamette rivers showed marked sexual dimorphism that has not been reported in any Manayunkia described to date, though it is apparent that this had been missed in M. speciosa. Accordingly, we describe a new taxon, Manayunkia occidentalis sp. nov., and show that it can host both C. shasta and P. minibicornis. We suspect that previous records of Manayunkia from Pacific Northwest watersheds are likely to be M. occidentalis sp. nov. and not M. speciosa. Sampling of Manayunkia from additional localities is underway to test if the novel Manayunkia species is the only freshwater fabriciid annelid present across the Pacific Northwest.